Bedengan Sebagai Teknik Budidaya Yang Efektif Untuk Lahan Rawan Banjir: Studi Kasus Di Desa Hilidundra, Kecamatan Lotu, Kabupaten Nias Utara - Arif Indra Jaya Gea; Natalia Kristiani Lase (Jurnal Ilmu Pertanian dan Perikanan, 2026)
Hilidundra Village in Lotu District, North Nias Regency, is one of the areas with a high level of flood vulnerability, especially during the rainy season. This condition hampers local agricultural productivity which is highly dependent on the weather. This study aims to evaluate the effectiveness of the raised bed technique in increasing crop yields on land prone to flooding. The study was conducted using qualitative and quantitative approaches through field observations, farmer interviews, and plant growth experiments on two land systems: using raised beds and without raised beds. The results showed that the raised bed technique was able to increase drainage efficiency, reduce plant damage due to flooding, and significantly increase agricultural productivity. This technique is recommended as a relevant and applicable adaptation solution for agricultural land in tropical areas that are prone to flooding.